Primary soft palate canine transmissible venereal tumour in a neutered Siberian husky dog (Canis lupus familiaris) - Hafezi, Bahareh; Kazemi Mehrjerdi, Hossein; Salari Sedigh, Hamideh; Rajabioun, Masoud; Mohri, Mehrdad (Veterinary Record Case Reports, 2024)
Abstract Canine transmissible venereal tumour is a type of neoplasm that can be transmitted through sexual contact in dogs. The occurrence of secondary oral canine transmissible venereal tumour is well documented in dogs; however, primary oral canine transmissible venereal tumour is uncommon. This report presents a rare case of a 2.5‐year‐old, neutered, male Siberian husky dog with an ulcerated mass on the soft palate that was undetected by clinical and radiological examinations, which was later diagnosed as a canine transmissible venereal tumour based on cytology without any genital manifestations. Chemotherapy with vincristine sulfate (5 weeks) resulted in complete recovery of the tumour without recurrence after 6 months. Based on our findings, we emphasise the importance of considering canine transmissible venereal tumour as a possible cause of extragenital masses even in neutered dogs.